Properties and Applications of Metal Phosphates and Pyrophosphates as Proton Conductors - Pérez-Colodrero, Rosario Mercedes; Olivera-Pastor, Pascual; Cabeza-Díaz, Aurelio; Bazaga-García, Montse (MDPI, 2022)
We review the progress in metal phosphate structural chemistry focused on proton conductivity properties and applications. Attention is paid to structure–property relationships, which ultimately determine the potential use of metal phosphates and derivatives in devices relying on proton conduction. The origin of their conducting properties, including both intrinsic and extrinsic conductivity, is rationalized in terms of distinctive structural features and the presence of specific proton carriers or the factors involved in the formation of extended hydrogen-bond networks. To make the exposition of this large class of proton conductor materials more comprehensive, we group/combine metal phosphates by their metal oxidation state, starting with metal (IV) phosphates and pyrophosphates, considering historical rationales and taking into account the accumulated body of knowledge of these compounds. We highlight the main characteristics of super protonic CsH2PO4, its applicability, as well as the affordance of its composite derivatives. We finish by discussing relevant structure–conducting property correlations for divalent and trivalent metal phosphates. Overall, emphasis is placed on materials exhibiting outstanding properties for applications as electrolyte components or single electrolytes in Polymer Electrolyte Membrane Fuel Cells and Intermediate Temperature Fuel Cells.
Keywords: Fosfatos; Protones; metal phosphate; proton conductivity; super protonic conductors; fuel cells; H-bond network; proton carriers